Paciente de sexo femenino de 77 años de edad que presenta diabetes mellitus tipo ii y sobrepeso. - Campuzano Monserrate, Karla Mercedes (2019)
Type II Diabetes Mellitus is a common problem in the health of older adults, in Ecuador, according to INEC, it is designated as the second origin of mortality, also being the main reason for mortality in women and third in men. In the country Diabetes prevails in the population between 10 and 59 years. The patient to be examined is an adult over 77 years of age weighing 65.9 kg and a 1.56 cm, was diagnosed with Type II Diabetes Mellitus 15 years ago. Go to your endocrinologist to consult because he has a lot of variation in his daily blood glucose rises with 120 mg / dl and goes to bed with 180 mg / dl despite taking his daily Amaryl 2mg 1 medicine, Galvus met 50/850 mg 1 with breakfast and snack. That is why this case study helps treatment through education, diet and physical activity. The patient must adapt to a nutritional plan with the purpose of improving her state of health that will be appropriate according to her needs and her intervention of the pathology with the intention of preventing aggravation and ailments of future complications.